Association Against the Prohibition Amendment records - Association Against the Prohibition Amendment
Chiefly anti-prohibition articles clipped from newspapers and magazines. Also includes a certificate of foundation, annual reports, pamphlets, bibliographies of anti-prohibition literature, and a mailing list.
Anti-prohibition organization.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Prohibition